New distributional records of Mecoptera (Insecta) from Colombia - Ardila-Camacho, Adrian; Vargas, Juan Felipe; Arango, Carlos Julio; García-García, Alexander; Machado, Renato Jose Pires (Papéis Avulsos de Zoologia, 2017)
We present new distributional records for two Colombian species of Bittacidae. Pazius convolutus García-García & Cadena-Castañeda, 2015 and Bittacus panamensis Byers, 1958 previously known from Cundinamarca department are herein newly recorded from Santander and Magdalena, respectively. In addition, we recorded Bittacus pignatelli Navás, 1932 in Colombia for the first time, increasing the number of species of Mecoptera in the country. Comments about mating behavior of P. convolutus, as well as a distribution map and a check-list of Colombian species of Mecoptera are included.